Parasocial Interactions and Relationships in Early Adolescence - Gleason, Tracy R.; Theran, Sally A.; Newberg, Emily M. (Frontiers in Psychology, 2017)
Parasocial interactions and relationships, one-sided connections imagined with celebrities and media figures, are common in adolescence but have received little descriptive or empirical attention in the developmental psychology literature. We asked 151 early adolescents (Mage = 14.8 years) to identify a famous individual of whom they are fond; we examined the type of celebrities chosen and why they admired them, and the relationships imagined with these figures across the entire sample and by gender. Adolescents emphasized highly salient media figures, such as actors, for parasocial attention. While different categories of celebrities were appreciated equally for their talent and personality, actors/singers were endorsed for their attractiveness more so than other celebrity types. Most adolescents (61.1%) thought of their favorite media figures as relationship partners, and those who did reported more parasocial involvement and emotional intensity than those who did not. Gender differences emerged in that boys chose more athletes than girls and were more likely to imagine celebrities as authority figures or mentors than friends. Celebrities afforded friendship for girls, who overwhelmingly focused on actresses. Variations in parasocial relationships may be linked to the social functions of parasocial processes in adolescent development.